The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1034/j.1600-0773.2000.pto870303.x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and Testosterone Modulate the Convulsant Actions of Pentylenetetrazol and Strychnine in Mice

Abstract: The influence of progesterone and testosterone on the incidence of seizures after administration of intraperitoneal pentylenetetrazol and subcutaneous strychnine was evaluated in mice. Pentylenetetrazol and strychnine were administered in doses that induced seizures in 40-50% of control mice in dioestrus (48 and 0.9 mg/kg, respectively). The percentage of seizures induced by pentylenetetrazol and strychnine was significantly lower in female mice in prooestrus/oestrus, when progesterone levels are high, than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The fact that a significantly higher proportion of neutered male dogs experienced cluster seizures compared to intact males might explain this finding. Whether testosterone possesses pro‐ or anticonvulsive properties is an ongoing subject of investigation . A seizure protective effect, through modulation of the GABA receptor driven by testosterone‐derived neurosteroid 3α‐androstanediol, has however been suggested in some in vivo rodent studies …”
Section: Discussionmentioning
confidence: 99%
“…The fact that a significantly higher proportion of neutered male dogs experienced cluster seizures compared to intact males might explain this finding. Whether testosterone possesses pro‐ or anticonvulsive properties is an ongoing subject of investigation . A seizure protective effect, through modulation of the GABA receptor driven by testosterone‐derived neurosteroid 3α‐androstanediol, has however been suggested in some in vivo rodent studies …”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, it has been claimed that strychnine can induce convulsions, and some researchers have used the kindling model to show that specific medicines are able to modulate convulsant actions. 11,12 Previous research has confirmed that the mechanism in nux vomica-induced epileptic seizures are related to the mechanisms underlying the effects of brucine and strychnine. Strychnine and brucine have been found to compete with the inhibitory neurotransmitter glycine, leading to epileptic seizures.…”
Section: Nux Vomicamentioning
confidence: 97%
“…In epilepsy, androgens can influence seizure susceptibility in males. 159–163 In males with epilepsy, lower levels of free testosterone and sexual dysfunction can be observed 164 but the directionality of this effect and whether treatments for epilepsy compound this relationship are not clear. 164 , 165 However, in animal studies, castrated rodents are more susceptible to pentylenetetrazol, picrotoxin, and perforant pathway stimulation-induced seizures compared with intact males, and testosterone administration decreases seizure activity in castrated males.…”
Section: Androgens and Adult Hippocampal Neurogenesis: Implications For Health And Diseasementioning
confidence: 99%
“… 164 , 165 However, in animal studies, castrated rodents are more susceptible to pentylenetetrazol, picrotoxin, and perforant pathway stimulation-induced seizures compared with intact males, and testosterone administration decreases seizure activity in castrated males. 159–161 There is also evidence to suggest that the testosterone metabolite 3α-diol is protective against gamma-aminobutyric acid (GABA) A receptor antagonist-induced seizures in male mice, 162 , 163 which is interesting as 3α-diol has a weak affinity for ARs. 41 However, the relationship between sex steroid hormones and epilepsy has proven difficult to discern as various factors such as experimental conditions and biological variability can greatly influence study outcomes (reviewed in Scharfman and MacLusky 166 ).…”
Section: Androgens and Adult Hippocampal Neurogenesis: Implications For Health And Diseasementioning
confidence: 99%